2018
DOI: 10.4108/eai.13-7-2018.156435
|View full text |Cite
|
Sign up to set email alerts
|

Control of energy efficient belt conveyor gearless drummotor

Abstract: There is a tendency for simplifying the construction of gears. Many manufacturers design gearless electric drives for power mechanisms like traction. Rejection of mechanical transmission and replacing obsolete induction motor with energy-efficient permanent magnet synchronous machine allow to increase electric drive reliability, reduce repair and maintenance costs, also improve the technological process and industrial safety. This article is devoted to questions of permanent magnet synchronous motor control fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In the operation of belt intermediate drives, it is necessary to control the motors both in steady and transient motion, i.e., variable material flow and start-up [24][25][26][27]. One of the solutions is the use of control systems based on vector inverters, with separate control of engine rpm and torque [28][29][30]. These types of solutions are successfully used in various types of real installations [12,[31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In the operation of belt intermediate drives, it is necessary to control the motors both in steady and transient motion, i.e., variable material flow and start-up [24][25][26][27]. One of the solutions is the use of control systems based on vector inverters, with separate control of engine rpm and torque [28][29][30]. These types of solutions are successfully used in various types of real installations [12,[31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the experience of operating plate conveyors at mining enterprises has shown that the use of modern frequency-controlled electric drives is a promising direction in improving the efficiency of operation of multi-motor plate conveyors, providing control of the speed of movement of the bearing web, control of load distribution between drives, elimination of equalizing forces in the conveyor traction circuit, automatic start of a multi-motor conveyor taking into account the elastic-viscous properties of tractionthe load-bearing canvas and a number of other factors [5][6][7][8].…”
mentioning
confidence: 99%